2017
DOI: 10.3390/su10010053
|View full text |Cite
|
Sign up to set email alerts
|

Review of Soil Organic Carbon Measurement Protocols: A US and Brazil Comparison and Recommendation

Abstract: Soil organic carbon (SOC) change influences the life-cycle assessment (LCA) calculations for globally traded bio-based products. Broad agreement on the importance of SOC measurement stands in contrast with inconsistent measurement methods. This paper focuses on published SOC research on lands managed for maize (Zea mays L.) in the U.S. and sugarcane (Saccharum officinarum L.) in Brazil. A literature review found that reported SOC measurement protocols reflect different sampling strategies, measurement techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…Certain articles were excluded due to inadequate results justification. Considering Scopus may fail to retrieve a significant percent of related works [56], previous reviews and surveys [7,9,19,27,38,46,54,[57][58][59][60][61][62][63][64][65] were further examined for related work and references from the selected articles were also evaluated, resulting in 28 articles in total.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain articles were excluded due to inadequate results justification. Considering Scopus may fail to retrieve a significant percent of related works [56], previous reviews and surveys [7,9,19,27,38,46,54,[57][58][59][60][61][62][63][64][65] were further examined for related work and references from the selected articles were also evaluated, resulting in 28 articles in total.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, to optimize the monitoring and mapping capacity, there is a need for consistent datasets able to provide reliable information for SOC content estimation [8]. Despite the progress achieved in estimating SOC dynamics by means of a number of research activities and projects, there is no internationally agreed definition of a standardized soil SOC information system [9]. This is partly because proper information integration at a scale to support complex strategies and monitoring approaches has until now been difficult and expensive to setup and be operational.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to address this problem using machine learning techniques, in the hope that this would produce more accurate results than linear regression [27,28,42,43]. As Davis et al [16] stated, the diverse and various methodologies for SOC estimation limit the researchers' ability of the to compare the results of their studies in order to generate conclusive results. Therefore, laboratory-based studies focus on finding the most accurate and effective approach for such a calibration.…”
Section: Multivariate Calibrationsmentioning
confidence: 99%
“…All analytical SOC measuring protocols have been thoroughly described in the literature [16], while remote sensing techniques for SOC estimation have been recently reviewed in detail [17]. However, there is a need to review the research work in laboratory and proximal sensing techniques in the VNIR-SWIR region, due to their significance on the development of nondestructive SOC estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Gross and Harrison (2018) found that core, clod, and excavation soil‐sampling methods produce very different bulk density results and that the commonly used core method consistently led to underestimated SOC levels at soil depths greater than 20 cm. A review by Davis et.al (2018) of 41 published SOC studies on U.S. corn and Brazilian sugarcane found a lack of consistency in sampling and laboratory analysis methods used in field research that reported SOC values.…”
Section: Assessing Soil Organic Carbonmentioning
confidence: 99%